Mathematical Analysis Of Herschel-Bulkley Fluid Model For Solute Dispersion In Blood Flow Through Narrow Conduits - Jaafar, Nurul Aini (2017)
The dispersion of solute play an important role in many chemical engineering, biomedical engineering and environmental sciences applications. The main interest of this study is the dispersion of solute (medicine) in blood (solvent) flow. An appropriate mathematical model is required to investigate the dispersion of solute in blood flow. In this study, the dispersion of solute in a blood flow is analyzed mathematically by treating the blood as a Herschel-Bulkley (H-B) fluid model through narrow conduits, namely, a circular pipe and a channel between two parallel flat plates. The steady dispersion of solute in blood flow without/with the presence of a chemical reaction between the solute and blood are considered.